the effect of soil texture with limited saltiness concentration - Baghdad Science Journal (مجلة بغداد للعلوم)
Found through the study of tissues Alnbarh and domestic focus where a direct impact on the development of the larvae mature into pupae and then to adults appeared to clay soils have a negative impact more than sandy soil at different concentrations salt where as it turns out that the percentage of evolution fly larvae worm Lhalzonnih of the ancient worldadult to have reached more than 80%